Jane Austen - Jones, Darryl 1967- (Macmillan Publishers Limited, 2001)
Darryl Jones offers a one volume study of Jane Austen that is both a coherent overview of the author's work and a survey of the current state of critical debate
Description based on publisher supplied metadata and other sources
Keywords: Austen, Jane -- 1775-1817; Austen, Jane; Roman